If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+3x-x=8+3(x+2)
We move all terms to the left:
5+3x-x-(8+3(x+2))=0
We add all the numbers together, and all the variables
2x-(8+3(x+2))+5=0
We calculate terms in parentheses: -(8+3(x+2)), so:We get rid of parentheses
8+3(x+2)
determiningTheFunctionDomain 3(x+2)+8
We multiply parentheses
3x+6+8
We add all the numbers together, and all the variables
3x+14
Back to the equation:
-(3x+14)
2x-3x-14+5=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9
| (v+4)^2-72=0 | | 2x^2=8x+32 | | c-9.75=20.75 | | 3/8e-17-5/9e=11 | | 6(x-5)+3(x-4)=4(x+2) | | 17x+2=47 | | Y=2E-08x^2 | | x/13=40/50 | | 4y-32=-4(y-2) | | 50+2x=5x+20 | | 12/5=31/x | | 5x=3x+180 | | .2x−5=17 | | -(1+7x)-6(-7-x=366 | | 3x=8.2 | | -3x^2+17x-2=3 | | 8x/(x-1)=10 | | 8x/(x-1)=20 | | 3x-10=20x+5 | | 1,2x²+0,5x²=1,7x² | | -72+y=-88 | | 2x^2-4x-42=0 | | 10+x+5=30 | | 3x^2+24x=10 | | 8x+14=2(-3x+12) | | c+2/3=4;c | | 3+(6/x)=8 | | 3x^2+36=-60 | | 6x=2(-3x-5)=154 | | 21+3x=18+x | | 625^2n-2=1/5 | | 9+3x=36+2x |